Assessing flood risks in the Taquari-Antas Basin (Southeast Brazil) during the September 2023 extreme rainfall surge - Mantovani, José [UNESP]; Alcântara, Enner [UNESP]; Pampuch, Luana A. [UNESP]; Praga Baião, Cheila Flávia; Park, Edward; Souza Custódio, Maria [UNESP]; Gozzo, Luiz Felippe [UNESP]; Bortolozo, Cassiano Antonio (Springer Nature, 2024)
This analysis delves into precipitation dynamics in the Bacia Taquari Antas region, with a focus on September 2023. Employing a multi-scale approach encompassing monthly, daily, and subdaily analyses, the study unveils a consistent precipitation distribution throughout the year. September 2023’s anomaly, the second-highest in the dataset, prompts investigation into potential climatic variability. Notably, the daily analysis highlights September 4th, 2023, as significant, emphasizing the importance of historical context in evaluating weather event severity. Subdaily scrutiny of September 4th reveals intense, localized precipitation, raising concerns about hydrological impacts such as flash floods. Positive trends in Rx5day (maximum consecutive 5-day precipitation amount) and R25 (number of days in a year when precipitation exceeds 25 mm) indices indicate an increase in heavy precipitation events, aligning with broader climate change concerns. Shifting focus to flood extent and impact assessment in the Taquari-Antas Basin, a simulation model depicts the temporal evolution of the flood, reaching its peak on September 4th. Examination of affected areas, rainfall volumes, and impacts on census sectors, cities, and buildings furnishes critical data for disaster management. This study contributes to localized precipitation comprehension and broader issues of climate trends, flood risk evaluation, and urban vulnerability, providing a basis for informed decision-making and resilient planning strategies.